Heavily Indebted Poor Countries Initiative and Multilateral Debt Relief Initiative : Statistical Update. (Policy Papers; Policy Paper ;, 2014)
The HIPC Initiative and MDRI are nearly complete with 35 countries having already reached the completion point under the HIPC Initiative. One country, Chad, remains in the interim phase. Debt relief under the Initiatives has substantially alleviated debt burdens in recipient countries and has enabled them to increase their poverty-reducing expenditure by two and a half percentage points between 2001 and 2013. Creditor participation in the Initiative has been strong amongst the multilateral and Paris Club creditors; however participation from the other creditor groups still needs to be strengthened. The total cost of debt relief to creditors under the HIPC Initiative is currently estimated to be USD 75.0 billion, while the costs to the four multilateral creditors providing relief under the MDRI is estimated to be USD 41.1 billion in end-2013 present value terms.